Just play co. : S-Urban Street /Ahmad Nazri Omar Latip ... [et al.] - Omar Latip, Ahmad Nazri; Zakaria, Khairul Adli; Maslani, Muhammad Farid Faiz; Khairul Munir, Khairul Syakir; Mohamad Fauzi, Muahmmad Sharul Aqwa (2017)
Just Play Co. is a company that provides for recreation and entertainment. Some of the recreation activity and entertainment that can be done are skateboarding, bike riding, scooter riding and last but not least, inline skating. Not only providing place to do such activities, we also give chance to people who does not have any of the activities equipment to use ours so that they can play too without costing them too much. S-Urban has stair steps, lots of banks and hips, bowl, pool with many different shapes and sizes, funbox, rails, handrails, flat bar rails, curbs, curve ledge and many more. S-Urban Street is a new business created especially for children, teenagers and adults. This kind of business was finalize and decided after a proper calculation and research was made. A huge amount of profit can be achieve as the business focus on rollerblading, skateboarding and many more, which are now greatly rose to popularity since 2007. Most important thing when the business has been commenced is that the customers find especially satisfied with the services. Furthermore, we hope that people find this place as a problem solver, relax area and stress relief kind of place. S-Urban Street not only focuses on profit, but tried to create a fun environment as people learn to play e-sport, thus in a future can create e-sport athletes in Malaysia.